ANALISIS HOLDING TIME POST WELD HEAT TREATMENT (PWHT) PADA PENGELASAN MATERIAL SA-213 GRADE T91 DENGAN SA-213 GRADE T22 UNTUK APLIKASI BOILER - Imam Khoirul Rohmat; Moh. Syaiful Amri; Mohammad Miftachul Munir; Hendri Budi Kurniyanto; M. Habib Muzzakki (Jurnal Rekayasa Mesin, 2023)
Superheater is one of the boiler components that works to heat the saturated steam coming out of the steam drum, by utilizing hot gases from combustion. In this study using Gas Tungsten Arc Welding (GTAW) and using SA-213 grade T91 and SA-213 grade T22, these two materials require Post Weld Heat Treatment (PWHT). One of the crucial factors in PWHT is holding time, because holding time aims to obtain a homogeneous temperature and homogeneous microstructure and can affect the mechanical properties of the material. This research was conducted to find out how the effect of PWHT holding time on SA-213 grade T91 and SA-213 grade T22 materials on the microstructure and hardness values. The results of the micro test show that the dominance of pearlite and martensite will decrease with increasing holding time, there is also a difference in microstructure grain size that will increase with increasing holding time which is associated with a decrease in value. The test results show that the hardness value will decrease with increasing holding time, especially in the weld metal area, getting the highest hardness value on the weld metal is in the specimen with a holding time of 15 minutes with a hardness value of 237.67 HVN and the lowest hardness value is in the specimen with holding time 45 minutes which is 201.1 HVN.